Role of Forensic accounting in Enhancing Cyber Fraud Prevention & Customer Confidence: A Comparative Study of Perspectives from Employees & Customers of Public and Private Sector Banks in India - Ms. Ayushi Garg, Dr. Monika Goel, Dr. Arkaja Garg (Journal of Daoist Studies, 2026)
The rapid technological digitalization in the new era of banking has increased the speed, accessibility, and comfort of carrying out financial transactions in India, while the increase in the cyber fraud activities due to digitalization of financial transactions has led to elevated financial losses, reputational damage and market competitiveness and declining customer confidence. In this regard, forensic accounting has evolved as crucial technique for identifying, examining, and mitigating financial fraud. This study explores the contribution of forensic accounting in curbing cyber fraud in public and private sector banks in India and assesses its impact on banking activities, client confidence, and institutional performance. It also considers obstacles such as inappropriate employee training, emerging cyber threats, and narrow customer awareness. To analyze the responses of banking personnel and customers, two separate questionnaires were prepared to be administered separately to these individuals in order to collect the primary data. Statistical techniques of Descriptive statistics and independent samples t-tests are used to evaluate the responses of 200 banking customers and 50 banking staff were recorded to conduct the analysis of the study. According to the results of the survey, employees of both public and private sector banks show highly positive responses regarding the effect of cybercrime on monetary transactions, customer confidence and ultimately on the profitability of the banking sector. Also, more than 88 per cent of employees in public and private sectors agreed that forensic accounting knowledge promote fraud control by improving fraud recognition, internal monitoring system, and regulatory compliance. The study emphasizes on the necessity of strengthening forensic accounting practices, employee training, and fraud mitigation strategies to enhance the security and credibility of Indian digital banking system.